Redundancy Elimination in the Future Internet - Din, Ikram Ud; Hassan, Suhaidi; Habbal, Adib M. Monzer (Springer, 2016)
Information-Centric Networking (ICN), also called Content-Centric Networking, is the most ascendant architecture for the Future Internet.In ICN, network nodes cache contents for a time before forwarding them to the end users.One of the applicable proposals to in-network caching, called Networking Named Content (NNC), suggests that caching contents at every node along the path can improve caching gain in terms of hit rate and content retrieval delay. However, storing content items at every node along the path can increase the chances of redundancy. Some strategies investigated that caching contents at only one intermediate node along the path can reduce the chances of redundancy. In addition, some strategies suggested that storing only popular contents can do better in performance, especially in reduced content redundancy. In this paper, we present a scheme, named Content Placement Mechanism (CPM), based on popularity of the contents that is suitable for redundancy elimination.